Impacts of climate change on tourism in the Mediterranean: Adaptive responses - Allen Perry (Fondazione Eni Enrico Mattei (FEEM), 2000)
Key sensitivities to Mediterranean tourism include drought and heatwaves, both of which are likely to increase with projected greenhouse warming. Adaptive responses must include lengthening of the present season and particularly taking care to cater for the increasing number of older people in the population of Northern European countries who will demand high environmental and accommodation standards and look for more bespoke holidays than the mass market tourist. Climate change in Northern Europe may affect the push-pull factors which currently favour a summer peak of tourists in many Mediterranean destinations. Infra structure and beaches may well be at risk from sea level rise and there are likely to be increased problems from forest fires, water supplies and hygiene.
Keywords: 330; Tourism; health; drought; heatwaves; illness; adaptive responses; Klimawandel; Internationaler Tourismus; Mittelmeerraum